Pengembangan Objek Wisata Pancuran Kuning untuk Meningkatkan Kepuasan Wisatawan di Desa Larike Kecamatan Lehitu Barat Kabupaten Maluku Tengah - Kelibia, Zaqia Zulfa; Manakane, Susan Evelin; Lasaiba, Mohammad Amin (Jurnal Pendidikan Geografi Unpatti, 2025)
Tourism is a strategic sector that significantly contributes to local economic development. This study examines the development strategy of Pancuran Kuning tourism destination in Larike Village, Leihitu Barat District, Central Maluku Regency, focusing on tourist satisfaction and its impact on community welfare. The research employed a qualitative approach with SWOT analysis to identify strengths, weaknesses, opportunities, and threats. Findings reveal that Pancuran Kuning possesses distinctive natural beauty, including pristine beaches, clear waters, and well-preserved coastal landscapes that attract visitors. However, limited accessibility, inadequate supporting facilities, and insufficient promotion remain major challenges. The recommended strategy emphasizes road improvements, additional facilities such as parking areas and recreational tools, as well as promotional efforts through digital media and collaboration with travel agencies.